PELATIHAN MICROSOFT EXCEL UNTUK ADMINISTRASI BISNIS DI BANK JASA JAKARTA - Januar Wahjudi (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2022)
This community service aims to provide information technology training, in order to improve the ability of Human Resources at Bank Jasa Jakarta, especially the use of Microsoft Excel in completing daily tasks. The benefits of this service in the form of training are expected that participants will experience an increase in the knowledge and skills needed in utilizing spreadsheet applications, especially Microsoft Excel in completing work, compiling reports, and compiling presentations in daily work routines. This community service in the form of training is carried out using presentation methods and guided practice step by step, where each participant carries out hands-on practice by being given materials in the form of electronic books, presentation materials for training guides, and worksheet files according to the training guidelines. Data on the development of the training participants were obtained from the initial questionnaire and evaluation questionnaire. From the data obtained information that the training has been carried out well, and the training materials have been well understood by the participants and participants have increased knowledge of the use of spreadsheet applications and expect advanced training topics